Pendekatan Statistik Deskriptif : Analisis Kepuasan Mahasiswa terhadap Fasilitas Kampus - Nur Zahra Maharani; Annisa Nur Safitri; Irfan Afandi Sipayung; Siddik Tambak; Adelyna Oktavia Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
The This study uses a descriptive statistical approach to analyze the level of student satisfaction with campus facilities at the State Islamic University of North Sumatra. Data were obtained through an online questionnaire using a simple random sampling method with 36 respondents. The questionnaire covered four categories of facilities: general, technology and accessibility, academic support, and campus and infrastructure. The analysis involved calculating percentage, probability, mathematical expectation, variance, and standard deviation. The results showed that library comfort had the highest satisfaction score (expected = 4.06), while the Wi-Fi connection had the lowest score (expected = 3.06, deviation = 1.39), indicating dissatisfaction and an uneven perception. Other aspects, such as academic guidance by lecturers (expectation = 3.86), toilet facilities (expectation = 3.83), and laboratories (expectation = 3.72), showed good satisfaction levels. These findings provide a strong basis for the campus to improve low-scoring areas and maintain areas that meet student expectations.